2022
DOI: 10.1038/s41393-022-00803-z
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception of individuals with spinal cord injury (SCI) during inpatient rehabilitation: a longitudinal study

Abstract: To assess overall illness perception and specific illness representations at admission and discharge of inpatient spinal cord injury (SCI) rehabilitation, and to detect associations between demographic and injury-related variables, and illness perception. SETTING: Seven Dutch SCI-specialised rehabilitation centres. METHODS: Participants aged >18 years with a recent SCI were screened for cognitive and emotional illness representations at admission and discharge with the Brief Illness Perception Questionnaire (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…At discharge there was no association with motor completeness. The findings of Kuiper et al [14] could suggest that those with motor complete SCI experience a stronger decrease of threat compared to those with motor incomplete SCI. Though one would indeed expect individuals with less severe SCI to have lower levels of helplessness than those with more severe injury, the findings in the current study supports research that demonstrates poorer psychological outcomes in individuals with motor incomplete injuries [59].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…At discharge there was no association with motor completeness. The findings of Kuiper et al [14] could suggest that those with motor complete SCI experience a stronger decrease of threat compared to those with motor incomplete SCI. Though one would indeed expect individuals with less severe SCI to have lower levels of helplessness than those with more severe injury, the findings in the current study supports research that demonstrates poorer psychological outcomes in individuals with motor incomplete injuries [59].…”
Section: Discussionmentioning
confidence: 95%
“…However, it is unclear whether the association with motor incompleteness is supported by literature. Kuiper et al [14] showed that motor complete SCI was associated with higher threat at admission. At discharge there was no association with motor completeness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation